Using Flash Platform to Realize the Video Question Answering System - Guie Jiao (Institute of Advanced Engineering and Science, 2014)
Video question answering system is designed and developed based on Flash platform technology, belongs of B / S (Browser / Server) structure, is used to meet the needs of specific groups’ teaching and studying. This paper describes core codes of database module and the real-time Q&A video module about video creating and video playback, also describes the relevant realization technology and other functional modules of the system. At last, it gives some modified suggestions. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4780